SIMULATION OF THE ORBITING SPACECRAFT TO ANALYSIS AND UNDERSTAND THEIR ROTATION BASED ON PHOTOMETRY - Koshkin, N. I.; Melikyants, S.; Korobeinikova, E.; Shakun, L.; Strakhova, S.; Kashuba, V.; Romanyuk, Ya.; Terpan, S. (Одеські астрономічні публікації, 2019)
Analysis of the photometric information allows to determine the parameters of spacecraft rotation. We will consider the light curves of a rotating satellite. Smooth changes in brightness, which are caused by diffuse scattering of sunlight, are characterized by the amplitude, quantity, shape and asymmetry of brightness variation during the rotation period of the body. In addition, the so- called “specular” flashes of light of very large amplitude are present on light curves. By analyzing the observed light curves of the inactive satellites Topex/Poseidon and Sich- 2, the determination of pole orientation these objects in space is demonstrated. To interpret the light curve's contained information, we are planning to creat optical- geometrical models of this satellite and simulated geometrical conditions by its orbit passages. Further comparison of the model and observed light curves should allow us to confirm the correctness of the satellite attitude determination. For the simulation, we used the MaxScript programming language, which allows to create a satellite model, and simulate the optical-geometric conditions of its passage, including the complex rotation of the spacecraft.